Application of the Multiplicative Method to Eliminate the Singularity in Integrals - Oblokulov S; Pardayev M. (International Journal on Human-Computing Studies, 2024)
In such cases it is necessary to construct exact quadratic formulas, as there are some errors in the approximate calculation of specific or non-specific integrals whose first-order derivatives become infinity in a given interval. In this work, the multiplicative method of loss of specificity under the integral of integral or non-specific integrals in which the first-order derivatives become infinity in a given interval is considered.